The Alexandreis of Walter of Châtillon : a twelfth-century epic : a verse translation - Walter, of Châtillon, active 1170-1180.; Townsend, David, 1955- (Philadelphia, Pa. : University of Pennsylvania Press, 1996)
David Townsend's translation - the first ever into English verse - affords modern readers a vivid sense of the aesthetic appeal and sophisticated artistry of Walter's poem. A concise introduction sets out the poem's background and significance in literary history, while also suggesting how Walter's text resonates with the literary sensibilities of our own times.
Townsend's explanatory notes, adapted in large part from glosses in the surviving manuscripts, allow modern audiences a remarkable glimpse into the ways in which medieval readers of the Alexandreis must have understood the poem.
Cover; Contents; Acknowledgments; Introduction; Select Bibliography; The Alexandreis; Prologue; Book One; Book Two; Book Three; Book Four; Book Five; Book Six; Book Seven; Book Eight; Book Nine; Book Ten; Notes; Index of Proper Names; A; B; C; D; E; F; G; H; I; J; L; M; N; O; P; R; S; T; U; V; W; X; Y; Z
Includes bibliographical references (pages xxvii-xxix) and index.
Print version record.
JSTOR
Keywords: Alexander, -- the Great, -- 356 B.C.-323 B.C. -- Romances; Alexander, -- the Great, -- 356 B.C.-323 B.C. -- Romances; Alexander, -- the Great, -- 356 B.C.-323 B.C.; Epic poetry, Latin (Medieval and modern) -- Translations into English; POETRY -- Epic; Epic poetry, Latin (Medieval and modern); Romances; Translations